On Cultural Significance of Russian Personal and Personal-Possessive Pronouns in Phraseological Units - I. Y. Graneva (Научный диалог)
The article is devoted to analysis of Russian personal pronouns ya ‘I,’ my ‘we,’ vy ‘you’ and personal possessive pronouns moy ‘my,’ nash ‘our,’ tvoy , vash ‘your’ as components of sustainable and declining phraseological units in the Russian speech in terms of expressing their culturally-important meanings. The purpose of the study is to describe the semantic properties (including the evaluation component of the semantics) of Russian phraseological units, incorporating these pronouns from the point of view of their expression of cultural information. The research is based on material extracted from phraseological dictionaries. The theoretical basis of the study are the methodological statements by A. Wierzbicka about description of culture through natural language, the idea of linguistic and cultural description of phraseological units by V. N. Teliya, the principles of linguistic conceptualization of the world, etc. The methods of the communicative-pragmatic analysis, cognitive analysis of the “language of culture,” referential analysis, conceptual analysis, functional-stylistic analysis of phraseological units are used. It is proved that the analyzed pronouns in phraseological units express a complex of national cultural-value meanings associated with particular prominence of the world of “our own” (circle “ours”) and its opposition to “other.” The practical significance of the work is related to the use of its results in teaching Russian as a foreign language and in the practice of compiling dictionaries of the “language of culture.”